Laser-based measurements of line strength, self- and pressure-broadening coefficients of the H35Cl R(3) absorption line in the first overtone region for pressures up to 1 MPa - Ortwein, Pascal; Woiwode, W.; Wagner, Steven; Gisi, M.; Ebert, Volker (Applied physics. B, Lasers and optics, 2010)
A high-resolution spectrometer based on a vertical-cavity surface-emitting laser (VCSEL) was developed and used to determine the line strength S(T0) =12.53(11) × 10−21 cm−1 /(molec cm−2 ) and the self-broadening coefficient γ 0HCl = 0.021787(61) cm−1 /atm of the R(3) absorption line in the first rovibrational overtone (2 ← 0) band of H 35 Cl. Furthermore, the first laser-based high-pressure study on the pressure broadening of HCl by He, N 2 and O 2(γ 0 N 2 = 0.07292(5) cm−1 /atm, γ 0 He =0.02113(1) cm−1 /atm, γ 0 O 2 = 0.03978(6) cm−1 /atm) is presented covering pressures of up to 1 MPa. The results are compared to previously available low-pressure data.